Sumbangan Paradigma Thomas S. Kuhn dalam Ilmu dan Pendidikan (Penerapan Metode Problem Based Learning dan Discovery Learning) - Afiq Fikri Almas (At-Tarbawi: Jurnal Kajian Kependidikan Islam, 2018)
Abstract: Thomas Kuhnâ€™s concept of scientific revolution has a historical role in the science of constructing the emergence of new science. It has the characteristics thinking and new philosophical model in the birth history of science and philosophy. The History of science is a basic science that is always marked by the strong paradigm and followed by the scientific revolution and is the starting point in studying fundamental issues in scientific epistemology for Thomas Kuhn. Thomas Kuhn termed this phase as a new science birth history phase, beginning with normal science, then emerged anomaly and crisis, and ended with the scientific revolution as a birth form of new science or new paradigm. Thomas Kuhn's paradigm can be contextualized in the science of education or donated to the world of education. The World of Education needs to design a teaching-learning process that can stimulate or provide anomalous data to learners, so as to transform their knowledge scheme toward a better scheme. Problem Based Learning and Discovery Learning became one of the methods of troubleshooting educational problems through experimental ways that make learners become the subject of education. This method is realized in line with has been formulated by Thomas S. Kuhn.Â Keywords: scientific revolution, education approach, problem based learning, and discovery learning